2002
DOI: 10.1034/j.1600-0706.2002.980311.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival in fluctuating bank vole populations: seasonal and yearly variations

Abstract: For most organisms, both within‐year (i.e. seasonal) and between‐year variations in demography are important components in shaping the population dynamic patterns observed on a multiannual scale. These two sources of variation have, however, rarely been studied simultaneously. Most of the recent work on small rodent population dynamics, for example, has focused on between‐year variation. Densities of seed‐ and fruit‐eating rodents, such as the bank vole (Clethrionomys glareolus), are in particular known to hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
48
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(52 citation statements)
references
References 41 publications
4
48
0
Order By: Relevance
“…Nevertheless, the range of survival rates in our study coincides with estimates found in a similar study based on trapping sessions with shorter time intervals. Crespin et al (2002) found a 7-day survival probability of 0.85-0.95, corresponding to a survival probability of 0.52-0.81 for 28 days. We estimated 28-day survival probabilities to be 0.76 and 0.55 for reproductively inactive and reproductively active PUUV IgG antibody-negative voles, respectively.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Nevertheless, the range of survival rates in our study coincides with estimates found in a similar study based on trapping sessions with shorter time intervals. Crespin et al (2002) found a 7-day survival probability of 0.85-0.95, corresponding to a survival probability of 0.52-0.81 for 28 days. We estimated 28-day survival probabilities to be 0.76 and 0.55 for reproductively inactive and reproductively active PUUV IgG antibody-negative voles, respectively.…”
Section: Discussionmentioning
confidence: 93%
“…Typically, smallmammal biologists distinguish juveniles from older individuals on the basis of body weight (sometimes in combination with pelage characteristics; Prevot-Julliard et al, 1999). We considered as juveniles and excluded all voles weighing #13 g (70 females and 55 males; see also Crespin et al, 2002). No reverse PUUV IgG seroconversions (i.e., potential disappearance of maternal antibodies) were detected in the remaining dataset.…”
Section: Capture-mark-recapture Datamentioning
confidence: 99%
See 2 more Smart Citations
“…However, by comparing the performance of climate and plant indices, our findings do suggest that the causal link between plants and herbivore may be more important to the class of small fossorial herbivores than that of large herbivores. There is ample evidence that variations in food availability are highly related to population dynamics of small temperate and arctic rodents (Laine & Henttonen 1983, Eurola et al 1984, Selås 1997, especially in seed eating forest rodents (Jensen 1982, Pucek et al 1993, Crespin et al 2002, Stenseth et al 2002b). Most importantly, hornbeam and oak seed crops incorporated in autoregressive models to analyse variation in annual numbers of wood mice and bank voles in the Bialowie .…”
Section: Discussionmentioning
confidence: 99%